Cluster observations and theoretical identification of broadband waves in the auroral region - M. Backrud-Ivgren; M. Backrud-Ivgren; G. Stenberg; M. André; M. André; M. Morooka; Y. Hobara; S. Joko; K. Rönnmark; N. Cornilleau-Wehrlin; A. Fazakerley; H. Rème (Annales Geophysicae, 2005)
Broadband waves are common on auroral field lines. We use two different methods to study the polarization of the waves at 10 to 180 Hz observed by the Cluster spacecraft at altitudes of about 4 Earth radii in the nightside auroral region. Observations of electric and magnetic wave fields, together with electron and ion data, are used as input to the methods. We find that much of the wave emissions are consistent with linear waves in homogeneous plasma. Observed waves with a large electric field perpendicular to the geomagnetic field are more common (electrostatic ion cyclotron waves), while ion acoustic waves with a large parallel electric field appear in smaller regions without suprathermal (tens of eV) plasma. The regions void of suprathermal plasma are interpreted as parallel potential drops of a few hundred volts.